Respostas
respondido por:
1
Desenvolvendo....
(x-2)² - x -1 = 0
x² - 4x+ 4 - x -1 = 0
x² - 5x + 3 = 0
a = 1
b= -5
c = +3
att Jhonny
(x-2)² - x -1 = 0
x² - 4x+ 4 - x -1 = 0
x² - 5x + 3 = 0
a = 1
b= -5
c = +3
att Jhonny
respondido por:
1
(x-2)² -x = 1
(x-2) (x-2) - x = 1
x² -2x -2x +4 -x= 1
x²-5x + 4 = 1
x² -5x + 4 - 1 = 0
x² -5x +3 = 0
a = 1
b = -5
c = 3
(x-2) (x-2) - x = 1
x² -2x -2x +4 -x= 1
x²-5x + 4 = 1
x² -5x + 4 - 1 = 0
x² -5x +3 = 0
a = 1
b = -5
c = 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás